FACTORS RELATED TO COMPUTER VISION SYNDROME (CVS) COMPLAINTS IN PROGRAMMERS DURING THE COVID-19 PANDEMIC - Marvita; Noeroel Widajati; Shafira Nurul Ramadhani; Wuri Handayani, Vitria (Faculty of Vocational Studies, Universitas Airlangga, 2024)
Background: Computer Vision Syndrome (CVS) symptoms can result from improper computer use. The manifestation of symptoms may encompass ocular strain, cephalalgia, ocular pain, xerophthalmia, diplopia, and visual blurring, influencing occupational efficiency. Purpose: To analyze factors related to CVS complaints among programmers at an IT consulting company in Jakarta. Method: A cross-sectional quantitative descriptive research involving 60 participants was conducted. The research examined the relationship between CVS complaints among programmers and several independent variables, including individual characteristics such as gender, age, visual aids, rest time, duration of computer use, work period, and workstation factors such as viewing distance from the screen to the horizontal eye line. The Spearman rank correlation test was utilized for data analysis. Result: Specifically, gender (sig.= 0.000), visual aids (sig.= 0.003), and the position of the top screen with the horizontal line of the eye (sig.= 0.029) were significantly related to CVS complaints. Age (sig.= 0.608), length of rest (sig.=0.055), duration of computer use (sig.= 0.138), work period (sig.= 0.717), and screen viewing distance (sig.= 0.058) did not show a significant relationship with CVS complaints. Conclusion: There is a relationship between gender, visual aids, and the position of the top of the screen with the horizontal line of the eye with CVS complaints. There is no relationship between age, length of rest, duration of computer use, working time, and screen viewing distance. Companies are expected to provide education regarding the correct use of computers, regular eye health checks, and enforce a 20-20-20 rule (20 minutes of rest, looking at objects 20 feet away for 20 seconds).